2010
DOI: 10.1038/onc.2010.490
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-Met downregulates TIGAR expression and reduces NADPH production leading to cell death

Abstract: c-Met represents an important emerging therapeutic target in cancer. Here, we demonstrate the mechanism by which c-Met tyrosine kinase inhibition inhibits tumor growth in a highly invasive Asian-prevalent head and neck cancer, nasopharyngeal cancer (NPC). c-Met tyrosine kinase inhibitors (TKIs; AM7 and c-Met TKI tool compound SU11274) downregulated c-Met phosphorylation resulting in markedly inhibited growth and invasion of NPC cells. Strikingly, inhibition of c-Met resulted in marked downregulation of TIGAR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 20 publications
5
45
0
Order By: Relevance
“…Taken together, our data suggest that TIGAR is induced in response to ROS, and previous work has shown that TIGAR can function to provide antioxidant defense (Bensaad et al 2006(Bensaad et al , 2009Lui et al 2011;Wanka et al 2012;Yin et al 2012;Cheung et al 2013). Normal and tumor intestinal crypts derived from constitutive TIGAR-null mice grew less well in 3D cultures, and these could be rescued with antioxidants such as N-acetyl L-cysteine (NAC) (Cheung et al 2013).…”
Section: Tigar Supports Intestinal Cell Growth By Limiting Damaging Rossupporting
confidence: 63%
See 1 more Smart Citation
“…Taken together, our data suggest that TIGAR is induced in response to ROS, and previous work has shown that TIGAR can function to provide antioxidant defense (Bensaad et al 2006(Bensaad et al , 2009Lui et al 2011;Wanka et al 2012;Yin et al 2012;Cheung et al 2013). Normal and tumor intestinal crypts derived from constitutive TIGAR-null mice grew less well in 3D cultures, and these could be rescued with antioxidants such as N-acetyl L-cysteine (NAC) (Cheung et al 2013).…”
Section: Tigar Supports Intestinal Cell Growth By Limiting Damaging Rossupporting
confidence: 63%
“…The first focuses on TIGAR, a protein that can control glucose metabolism and helps to maintain NADPH levels to regenerate glutathione (GSH), a key intracellular antioxidant. Loss of TIGAR expression leads to increased ROS, and while this is not obviously detrimental to normal growth and development, in most model systems, this results in defects in both proliferation and survival following stress (Bensaad et al 2006(Bensaad et al , 2009Lui et al 2011;Wanka et al 2012;Yin et al 2012). In the mouse intestine, loss of TIGAR can decrease the proliferation that accompanies tissue regeneration after genotoxic stress and limit the hyperproliferation seen in Wnt-driven adenoma through the failure to limit ROS (Cheung et al 2013).…”
mentioning
confidence: 99%
“…Alternatively, MUC1-C could contribute to stability of the TIGAR protein, such that inhibition of MUC1-C promotes TIGAR turnover. Inhibition of the MET receptor tyrosine kinase also down-regulates TIGAR expression; 31 however, there is presently nothing known about the mechanisms responsible for the regulation of TIGAR at the transcriptional or posttranscriptional levels. Given the finding that inhibition of MUC1-C increases ROS levels, the present studies examined whether oxidative stress contributes to the down-regulation of TIGAR expression.…”
Section: Muc1-c Regulates Tigar Expression In Multiple Myeloma Cellsmentioning
confidence: 99%
“…[15][16][17][18] Over-expression of MET has also been detected in cell lines established from Asian-prevalent head and neck cancer, nasopharyngeal cancer, pediatric tumors including osteogenic sarcoma and neuroblastoma, and hematopoietic malignancies including multiple myeloma and adult T-cell leukemia. [19][20][21][22][23] Constitutive MET activation due to MET amplification and/or MET mutation has been found to be a driver of proliferation and survival. MET expression correlates with an aggressive phenotype and poor prognosis.…”
Section: Met and Cancermentioning
confidence: 99%